Strategi Respon atas Digitalisasi Bisnis pada Perempuan Pelaku Usaha Mikro dan Kecil - Yasmine Nasution; Muthia Pramesti (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2024)
Institutional theory highlights that organizational success relies not only onresource availability but also on acceptance within its environment.Institutional isomorphism refers to the tendency of organizations within thesame industry to adopt similar structures and strategies due to sharedenvironmental pressures. In the context of micro and small enterprises(MSEs), digitalization has become a pivotal factor influencing businessprocesses. Female MSEs exhibit diverse responses to digitalization, driven bythe COVID-19 pandemic and market demands to enter digital commerce. Thisstudy investigates the strategies female MSEs employ to adapt to digitaltechnology. Using a qualitative approach, in-depth interviews were conductedin September 2022 with female MSEs in Depok. The findings reveal thatnormative and mimetic isomorphism are dominant strategies, while coerciveisomorphism is absent. Challenges in adopting digitalization stem from bothpersonal and external factors. Despite these obstacles, female MSEs recognizethe significance of digitalization for business sustainability. To addressadaptation issues, many rely on support from family and communitynetworks, facilitating the integration of digital tools into their operations. Thiscollaborative approach underscores the importance of social support inovercoming barriers to digital transformation within MSEs.